Squamous cell carcinoma of uterine cervix metastatic to the axillary lymph node. Issue 7 (12th July 2021) - Chundriger, Qurratulain; Chishti, Uzma; Idrees, Romana
Abstract : We report a case of an elderly woman, presenting with vesicouterine fistula and enlarged axillary lymph nodes. She had been diagnosed with cervical squamous cell carcinoma (SCC) in April 2015, for which she had received brachytherapy and concurrent chemoradiation therapy. The presence of enlarged axillary lymph nodes raised a suspicion for breast cancer with axillary metastases, but the bilateral mammograms did not show any discrete lesion in both breasts. The biopsy from axillary lymph node showed metastatic SCC, with block positivity for P16, confirming the origin from known cervical primary. Axillary lymph nodes are the least likely to be involved by tumours arising in the pelvis, as the lymphatic drainage of this region goes directly to the systemic circulation via the para-aortic lymph nodes and thoracic ducts. A complete clinical history is essential in such cases, to avoid misdiagnosis. Positron emission tomography CT helps in this regard.